Projective light-sheet microscopy with flexible parameter selection - Bingying Chen; Bo-Jui Chang; Stephan Daetwyler; Felix Zhou; Shiv Sharma; Donghoon M. Lee; Amruta Nayak; Jungsik Noh; Konstantin Dubrovinski; Elizabeth H. Chen; Michael Glotzer; Reto Fiolka (Nature Communications, 2024)
Abstract Projection imaging accelerates volumetric interrogation in fluorescence microscopy, but for multi-cellular samples, the resulting images may lack contrast, as many structures and haze are summed up. Here, we demonstrate rapid projective light-sheet imaging with parameter selection (props) of imaging depth, position and viewing angle. This allows us to selectively image different sub-volumes of a sample, rapidly switch between them and exclude background fluorescence. Here we demonstrate the power of props by functional imaging within distinct regions of the zebrafish brain, monitoring calcium firing inside muscle cells of moving Drosophila larvae, super-resolution imaging of selected cell layers, and by optically unwrapping the curved surface of a Drosophila embryo. We anticipate that props will accelerate volumetric interrogation, ranging from subcellular to mesoscopic scales.